ANALYZING THE IMPACT OF ANDROID USAGE ON SOCIAL INTERACTION OF ELEMENTARY SCHOOL STUDENTS - Uswah, Atiq Yuftriyah; Mukni’ah, Mukni’ah; Hartono, Hartono (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
Android affects not only the lives of adults, but also the daily lives of elementary school-aged children. This includes how these children behave, act, or think, all of which contribute to the lack of effective interactions between kids and their parents, teachers, friends, peers, and the people around them. In order to describe the effects of Android use on social interaction among fifth grade kids at MIN 5 Jember, the researchers set out to perform this study. With the sort of case study employed in the research, qualitative research techniques were applied. The researcher is a key tool in research, and supporting tools like interview and observation guidelines can help the researcher collect data. Data collection activities are obtained through in-depth interview techniques, observation, and documentation studies. Researchers employed the Miles and Huberman approach, which was completed in four stages, to analyse the data. Source triangulation was employed by the researchers in the interim to ensure the accuracy of the data. The results of the research show that children who use androids excessively can develop ego and individualism. Particularly, lack of responsibility and supervision will have an effect, leading to a lack of direct social interaction, turning children into anti-social and reclusive individuals.